Claiming land, sustaining life: Feminist political ecology of women’s collective action in Pari Island - Prawitasari, Shanti Ayu; Sinaga, Hariati; Viajar, Verna Dinah Q. (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
This article examines women’s collective action against land grabbing on Pari Island, Jakarta Bay, through the framework of Feminist Political Ecology (FPE). Land grabbing in Indonesia’s coastal areas often marginalises local communities, with women disproportionately affected due to their reliance on land and marine resources for subsistence and livelihoods. Using a qualitative case study approach, the research draws on in-depth interviews and focus group discussions (FGDs) with four women from the Women’s Group in Pari Island. The findings show that women’s struggles extended beyond direct protest to include the development of gendered ecological knowledge—such as vegetable gardening and mangrove planting—and grassroots activism through arisan, beach management, and solidarity networks. These are transforming everyday ecological labour into claims over space, rights, and justice. Despite persistent challenges—restrictive gender norms, criminalisation, stigma, and the lack of generational succession—women secured small but significant victories. These included the Ombudsman’s recognition of maladministration, political support from the UN Special Rapporteur on the Right to Food, and local economic strengthening through community-based tourism. The study emphasises the importance of integrating gender perspectives into the analysis of coastal land conflicts and calls for greater institutional support for women’s leadership, education, and advocacy in sustainable resource governance.